Juvenile elastoma. Case report. - Sotiriou, E.; Sotiriadis, D. (European Journal of Pediatric Dermatology, 2003)
Connective tissue nevi are circumscribed hamartomatous malformations of the dermal extracellular matrix. They represent the cutaneous component of a number of inherited disorders, such as Buschke-Ollendorff syndrome, or occur as isolated lesions without any confirmed genetic basis. We report a 7-year-old girl with juvenile elastoma. After the clinical and radiological examination of both the patient and her parents, it was clear that the patient had a connective tissue nevus - classified under the elastic naevi - without osteopoikilosis.